2018
DOI: 10.4103/ija.ija_670_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect site concentration of propofol at induction and recovery of anaesthesia - A correlative dose-response study

Abstract: Background and Aims:Sound knowledge about effect site concentration (Ce) of propofol aids in smooth induction, maintenance and early recovery. We studied the correlation between Ce of propofol at loss of response to verbal command and recovery concentration using target-controlled infusion (TCI) in Indian patients who underwent spine surgeries.Methods:Ninety patients undergoing spine surgeries were included. Total intravenous anaesthesia (TIVA) technique with TCI for propofol using modified Marsh model was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Sukumar et al . conducted a study comparing the effect of an IV bolus of propofol at anaesthesia induction and recovery and suggested that propofol aids in smooth anaesthesia induction, maintenance and early recovery 16. Moreover, Mishra et al .…”
Section: Discussionmentioning
confidence: 99%
“…Sukumar et al . conducted a study comparing the effect of an IV bolus of propofol at anaesthesia induction and recovery and suggested that propofol aids in smooth anaesthesia induction, maintenance and early recovery 16. Moreover, Mishra et al .…”
Section: Discussionmentioning
confidence: 99%
“…Variability in the onset and offset profile of an anesthetic drug is likely due to the factors influencing the pharmacokinetics and the relationship between drug concentrations and their effect [ 16 ]. Ce rather than Cp better reflects the clinical effects of intravenous hypnotics [ 10 , 11 ]; however, administering remimazolam via effect-site target-controlled infusion method is still unavailable. In terms of optimal dosage adjustment, therefore, it would be clinically advantageous if the individual remimazolam Ce could be simulated and applied in clinical practice rather than simply traditional observations of autonomic response along with monitoring of depth of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…As most drugs act at sites remote from the bloodstream, hysteresis, a phenomenon denoting time lag between the measured plasma drug concentration and the observed drug effect may occur [ 9 ]. Therefore, the pharmacologic effect can be determined based on either the plasma concentration (Cp) or effect-site concentration (Ce); however, Ce rather than the Cp reflects the clinical effects of intravenous anesthetics better [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Propofol seems to be an attractive option as it has a favourable pharmacokinetic profile, with a rapid onset of action and early recovery with easy titration of level of sedation. [ 1 ] Single or repeated boluses of propofol for sedation have a rapid onset but lead to unstable plasma levels with the consequent adverse effects like respiratory and haemodynamic instability at peak concentrations and inadequate level of sedation at trough plasma levels. Continuous infusion using manual infusion pump following a bolus injection often leads to increasing blood concentration of propofol over time, requiring repeated adjustments to maintain adequate level of sedation.…”
Section: Introductionmentioning
confidence: 99%